Micro and Macro Effects of Unemployment Insurance Policies: Evidence from Missouri - Karahan, Fatih; Mitman, Kurt; Moore, Brendan (Journal of Political Economy, 2025)
We develop a method to jointly measure the response of worker search effort (micro effect) and vacancy creation (macro effect) to changes in the duration of unemployment insurance (UI) benefits. To implement this approach, we exploit an unexpected cut in UI durations in Missouri and provide quasi-experimental evidence on the effect of UI on the labor market. In our baseline specification, the data indicate that the cut in Missouri increased job-finding rates by 12% by raising firm vacancy creation and the search effort of unemployed workers. Both channels contribute roughly equally to the total effect.